2021
DOI: 10.3389/fphar.2020.613883
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 Suppresses Cardiomyocytes Apoptosis in CVB3-Induced Myocarditis Via Survivin

Abstract: Background: Viral myocarditis (VMC) is a common inflammatory cardiovascular disease with unclear mechanisms, which mainly affects children and adolescents. Apoptosis is the key to CVB3-induced myocarditis, and blocking this process may be beneficial to the therapy of VMC. Hence, this study aimed to explore the protective function of STAT3 on cardiomyocyte apoptosis of VMC and its underlying mechanisms.Methods and Results: In this research, we confirmed that STAT3 was significantly activated in both animal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In addition to natural variations from animal to animal, an issue confounding in vivo studies is that target protein expression in signaling pathways is activated for a while but is then deactivated or degraded. This limitation could be avoided by using an adjunct in vitro group, as has been implemented in animal studies measuring cell lysates in vitro and tissue lysates in vivo [ 56 , 58 , 60 ]. Employing an in vitro model in future investigations may improve the results’ reliability.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to natural variations from animal to animal, an issue confounding in vivo studies is that target protein expression in signaling pathways is activated for a while but is then deactivated or degraded. This limitation could be avoided by using an adjunct in vitro group, as has been implemented in animal studies measuring cell lysates in vitro and tissue lysates in vivo [ 56 , 58 , 60 ]. Employing an in vitro model in future investigations may improve the results’ reliability.…”
Section: Discussionmentioning
confidence: 99%
“…Upon stimuli, neuroin ammation is evoked and coupled with the increased secretion of pro-in ammatory cytokines, which exacerbates neurotoxicity and results in irreversible neuronal apoptosis (Seshadri 2021;Hong et al 2020). Apoptosis, one type of programmed cell death, is regulated principally by interactions within the B-cell lymphoma-2 (Bcl-2) family of proteins (Ney et al 2021; Wang et al 2020); among them, Bcl-2 and Bcl-2 associated X protein (Bax) are the vital members, which mediate multiple effectors thereby activating caspases (Reyna et al 2017;Yang et al 2020). Especially, activation of caspase 3, an eventual protein in the apoptotic cascade, leads to neuronal apoptosis (Chung et al 2018;Huang et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, phosphorylated STAT3 Tyr705 was almost undetectable. Previous studies showed that the activation of STAT3 protected cardiomyocytes against apoptosis ( Wang et al, 2020 ). This study supports the protective effect of IL-13 on the myocardium to a certain extent based on the activation of STAT3.…”
Section: Discussionmentioning
confidence: 99%